2017
DOI: 10.1016/j.bbrc.2017.04.112
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia exposure disrupts adrenomedullin signaling in newborn mice: Implications for lung development in premature infants

Abstract: Hyperoxia contributes to the development of bronchopulmonary dysplasia (BPD), a chronic lung disease of human infants that is characterized by disrupted lung angiogenesis. Adrenomedullin (AM) is a multifunctional peptide with angiogenic and vasoprotective properties. AM signals via its cognate receptors, calcitonin receptor-like receptor (Calcrl) and receptor activity-modifying protein 2 (RAMP2). Whether hyperoxia affects the pulmonary AM signaling pathway in neonatal mice and whether AM promotes lung angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…Hyperoxia exposure in the neonatal period results in impaired nephrogenesis via the downregulation of HIF-1 α [10], which is consistent with our observation that neonatal hyperoxia blunted the expression peak of HIF-1 α in the proximal tubules. A blunted expression peak in response to neonatal hyperoxia is also observed in other tissues [52]. HIF-1 α can trigger apoptosis in renal tubular epithelial cells [53], which is consistent with our observation that proximal tubular apoptosis is positively correlated to the expression of HIF-1 α on the 14th postnatal day.…”
Section: Discussionsupporting
confidence: 91%
“…Hyperoxia exposure in the neonatal period results in impaired nephrogenesis via the downregulation of HIF-1 α [10], which is consistent with our observation that neonatal hyperoxia blunted the expression peak of HIF-1 α in the proximal tubules. A blunted expression peak in response to neonatal hyperoxia is also observed in other tissues [52]. HIF-1 α can trigger apoptosis in renal tubular epithelial cells [53], which is consistent with our observation that proximal tubular apoptosis is positively correlated to the expression of HIF-1 α on the 14th postnatal day.…”
Section: Discussionsupporting
confidence: 91%
“…For example, in endothelial cells, the antirheumatic drug leflunomide attenuated oxidative stress in fetal human pulmonary endothelial cells that was elicited by hyper-oxia, through superoxide dismutase 2 (Sod2) and catalase (Cat), although endothelial cell function was not addressed. Adrenomedullin was also demonstrated to attenuate the deleterious impact of hyperoxia in fetal human pulmonary artery endothelial cells, this time on extracellular signal-regulated kinase (ERK) 1/2 phosphorylation, where endothelial cell functions such as tube formation were preserved (380). These data are in line with the suggestion from the same group that hyperoxia disrupted ERK1/2 signaling and ERK1/2-dependent angiogenesis in vitro (378).…”
Section: New Interventional Strategies To Drive Alveolarizationsupporting
confidence: 80%
“…Therefore, mice are one of the most commonly utilized laboratory animals to model human developmental lung disease such as BPD. We recently showed that neonatal hyperoxia exposure-induced alveolar and pulmonary vascular development abnormalities persists at four weeks of life (Menon et al, 2017). Because BPD infants have anatomical lung abnormalities that persist into adulthood, we evaluated the effects of neonatal hyperoxia exposure on alveolar and pulmonary vascular morphology in mice at eight weeks of age (equivalent to a human age of 21.5 years; (Dutta and Sengupta, 2016)).…”
Section: Resultsmentioning
confidence: 99%